Analysis of the Influence of Consumer Perception, Innovation and Product Quality on Purchasing Decisions of Travelers Consuming Traditional Getuk Goreng Foods in the Middle Sokaraja Village Sokaraja District - Elizabeth Tika Kristina Hartuti; Cornelia Dumarya Manik (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2020)
The company tries to create a product of course with good quality so consumers are interested in buying the product being sold. This study aims to determine the effect of consumer perceptions, innovation and product quality on purchasing decisions of tourists consuming traditional getuk goreng food in Sokaraja Tengah Village, Sokaraja District. The method used was explanatory research with a sample of 96 respondents. The analysis technique uses instrument testing, classical assumption test, regression testing, correlation coefficient, coefficient of determination and hypothesis testing. The results of this study consumers' perceptions significantly influence purchasing decisions by 31.9%, hypothesis testing obtained significance 0,000 <0.05. Innovation has a significant effect on purchasing decisions by 41.4%, hypothesis testing obtained significance 0,000 <0.05. Product quality has a significant effect on purchasing decisions by 26.9%, hypothesis testing obtained significance 0,000 <0.05. Consumer perception, innovation and product quality simultaneously have a significant effect on purchasing decisions by 50.1%, the hypothesis test obtained significance of 0,000 <0.05. Purchasing decisions significantly influence consumer satisfaction by 45.5%, hypothesis testing obtained significance 0,000 <0.05.